KEPUASAN DAN PRODUKTIVITAS KERJA KARYAWAN SAAT BEKERJA DARI RUMAH STUDI KASUS PADA PT. IMS MADIUN - Rohmad Satrio Nugroho; Karuniawati Hasanah (CAPITAL: Jurnal Ekonomi dan Manajemen, 2022)
Employee job satisfaction and productivity when working from home is influenced by several factors, including job characteristics, individual work styles, and household characteristics. This study aims to determine the effect of job characteristics, individual work styles, and household characteristics on job satisfaction and work productivity. In addition, this research aims to determine the indirect effect of job characteristics, individual work styles, and household characteristics on work productivity through job satisfaction as an intervening variable. The research was conducted at PT. INKA Multi Solutions Madiun. The method in this study was a quantitative method. The population and research sample were employees of PT. INKA Multi Solusi (IMS) Madiun which carried out work from home totals 104 employees. Sampling using the saturated sampling technique. The research instrument used a questionnaire via google form. The data analysis technique used Path Analysis with the IBM SPSS 25 program. The results show that job characteristics and work style have a positive and significant effect towards job satisfaction and productivity of PT. IMS Madiun while working from home. Meanwhile, household characteristics have no significant positive effect on job satisfaction and do not affect the work productivity of PT. IMS Madiun while working from home. Next, job satisfaction has a positive and significant effect on the work productivity of PT. IMS Madiun while working from home. Other results state that individual work characteristics and work styles have a positive and significant effect on work productivity through job satisfaction of employees of PT. IMS Madiun. Meanwhile, household characteristics have no significant positive effect on work productivity through job satisfaction of employees of PT. IMS